PENGARUH PERILAKU BULLYING TERHADAP INTERAKSI SOSIAL PADA REMAJA - Romadhoni, M. Tri Bagas; Heru, Maulidiyah Junnatul Azzizah; Rofiqi, Ach.; Hasanah, Zullul Warquatul; Yani, Vivin Anda (Jurnal Keperawatan Profesional, 2023)
Bullying is a very bad or deviant behavior because bullying behavior has a serious impact on the mental development of an individual, both children and adolescents. Objective: to determine the effect of bullying behavior on social interaction in adolescents.  Methods: The sources of the articles used were obtained from searches through the Science Direct database, Google Cindekia and Google Scholar. Article search is restricted from 2016-2021. After the article is obtained, then the article is reviewed until the stage of making a literature review. The keywords used in the article search were “bullying behavior” “social interaction” “Adolescents”. This literature review uses 15 articles that meet the inclusion criteria. Results: The effect of bullying behavior from the research reviewed is very influential on social interaction in adolescents.  Conclusion: Based on the results of a review of 15 journals on the influence of bullying behavior, it is very influential on social interaction in adolescents